Human Metapneumovirus Escapes NK Cell Recognition through the Downregulation of Stress-Induced Ligands for NKG2D - Mohammad Diab; Dominik Schmiedel; Einat Seidel; Eran Bacharach; Ofer Mandelboim (Viruses, 2020)
The Pneumoviridae family includes human metapneumovirus (HMPV) and human orthopneumovirus, which is also known as a respiratory syncytial virus (HRSV). These are large enveloped, negative single-strand RNA viruses. HMPV and HRSV are the human members, which commonly infect children. HMPV, which was discovered in 2001, infects most children until the age of five, which causes an influenza-like illness. The interaction of this virus with immune cells is poorly understood. In this study, we show that HMPV evades natural killer (NK) cell attack by downregulating stress-induced ligands for the activating receptor NKG2D including: Major histocompatibility complex (MHC) class I polypeptide-related sequences A and B (MICA, MICB), UL16 binding proteins ULBP2, and ULBP3, but not ULBP1. Mechanistically, we show that the viral protein G is involved in the downregulation of ULBP2 and that the viral protein M2.2 is required for MICA and MICB downregulation. These findings emphasize the importance of NK cells, in general, and NKG2D, in particular, in controlling HMPV infection, which opens new avenues for treating HMPV.